Influence of international co-authorship on the research citation impact of young universities - Khor, Khiam Aik (2020)
We investigated the effect of international collaboration (in the form of international co-authorship) on the impact of publications of young universities (< 50 years old), and compared to that of renowned old universities (> 100 years old). The following impact indicators are used in this study, they are: (1) the 5-year citations per paper (CPP) data, (2) the international co-authorship rate, (3) the CPP differential between publications with and without international co-authorships, and (4) the difference between the percentage of international co-authored publications falling in the global top 10 % highly cited publications and the percentage of overall publications falling in the global top 10 % highly cited publications (D%Top10%). The increment of 5-year (2010–2014) field weighted citation impact (FWCI) of internationally co-authored papers over the 5-year overall FWCI of the institutions in SciVal is used as another indicator to eliminate the effect of discipline difference in citation rate. The results show that, for most top institutions, the difference between the citations per paper (CPP) for their publications with and without international co-authorship is positive, with increase of up to 5.0 citations per paper over the period 1996–2003. Yet, for some Asian institutions, by attracting a lot of researchers with international background and making these collaborating ‘‘external’’ authors as internal researchers, these institutions have created a special kind of international collaboration that are not expressed in co-authorship, and the CPP gaps between publications with and without international co-authorship are relatively small (around 0–1 citations per paper increment) for these institutions. The top old institutions have higher CPP than young institutions, and higher annual research expenditures; while young universities have a higher relative CPP increment for the current 5-year period over the previous 5-year period. The D%Top10% for international co-authored publications is generally higher than that for all journal publications of the same institution. With the increase of international co-authorship ratio, the mean geographical collaboration distance (MGCD, an indication of increased international co-authorship) of one institution based on the Leiden Ranking data also increases, and young institutions have relatively higher CPP increment over MGCD increment. International co-authorship has a positive contribution to the FWCI of the institution, yet there are untapped potential to enhance the collaboration among young institutions.